ANALISIS EFISIENSI STRUKTUR GEDUNG PROYEK PEMBANGUNAN GEDUNG RAWAT INAP VIP RUMAH SAKIT UMUN DAERAH CIDERES KABUPATEN MAJALENGKA - Fahrul Rozi (PROCEEDING STIMA)
Planning Structure of the Majalengka Garden Hotel Building according to SNI 03-2847-2002 article 23.2.3, states that for areas with earthquake risk medium, must be used special or medium moment bearer system, or an ordinary concrete structure or walls system specifically for carrying the styles caused by an earthquake. The building was designed using the Resisting Frame System Special Moments (SRPMK). Strongly designed against several combinations loading such as dead load, live load, and earthquake load. This system planned to use the concept of strong columns - weak beams, where the elements vertical of the structure (column) is stronger than the horizontal element of the structure (beam) so that the plastic joint is formed first on the beam section. Joint-joint on beam-column relationships must also be well designed so as not to occur collapse. The results of structural analysis using SAP2000 version 14 software for help determine the forces acting on the structure, then used to calculate reinforcement and check the strength of the structure. The stages of planning structures include analyzing the conditions and conditions soil, design the configuration of the building structure and its structural system, determination of the loads acting on the structure, determination of dimensions and reinforcement of structural elements, and finally design drawing.